Prevalence and Antibiogram of Bacterial Uropathogens from a Tertiary Care Hospital of Eastern Nepal - Shrestha, Kewal; Singh , Prabhat Kumar; Yadav, Kumari Ragani; Singh, Ganesh Kumar (Journal of Nobel Medical College, 2023)
Background: Urinary tract infection (UTI) is defined as growth of micro-organisms >105 CFU/ml in mid-stream urine samples. [1] Globally, urinary tract infection is considered a major public health concern with the second most common bacterial infection affecting individuals of different ages. It is estimated that worldwide 150 million cases of UTI occur per year and bacteria are responsible for about 95% of all the cases with each year. [3, 4] This study was designed to describe the pattern of microorganisms causing UTI and their antibiotic sensitivity.Materials and Methods: This is a hospital based cross-sectional study conducted in the Department of Microbiology from January 2022 to June 2022 after taking ethical approval from Institutional Review Committee, Nobel Medical College and Teaching Hospital, Biratnagar, Nepal. The patient profiles or records visiting a tertiary care hospital of both sex and every age group who were having symptoms and clinical diagnosis of urinary tract infection were included.Results: A total of 2247 urine samples were collected, 501(22.29%) of the urine sample yielded significant growth of uropathogenes. The most common bacteria was found to be Escherichia coli (E. coli) that accounts for 73.05% followed by Enterococcus species 11.57%, Klebsiella pneumoniae 8.98% and amikacin and nitrofurantoin was found to be the most sensitive antibiotic to gram negative uropathogens.Conclusion: The prevalence of uropathogenes was found to be higher in our study. Significant bacteriuria was seen in the female than male. The total number of patient with culture positivity was higher in younger age groups with high frequency of antibiotic resistance